The order of things - Langley, Kaija (Nancy Paulsen Books, 2023)
Eleven-year-old April Jackson loves playing the drums, almost as much as she loves her best friend, Zee, a violin prodigy. They both dream of becoming professional musicians one day. When Zee starts attending a new school that will nurture his talent, April decides it's time for her to pursue her dreams, too, and finally take drum lessons. She knows she isn't very good to start, but with Zee's support, she also knows someday she can be just as good as her hero, Sheila E., and travel all around the world with a pair of drumsticks in her hand. When the unthinkable happens and Zee suddenly passes away, April is crushed by grief. Without Zee, nothing is the way it's supposed to be. Zee's Dad isn't delivering the mail for his postal route like he should. April's Mom is suddenly dating someone new who is occupying too much space in their lives. And every time April tries to play the drums, all she can think about is Zee. April isn't sure how to move on from the awful feeling of being without Zee. Desperate to help Papa Zee, she decides to secretly deliver the mail he's been neglecting. But when on her route she discovers a classmate in trouble, she doesn't second guess what she knows is the right thing to do.